Non-Compliance in Public Financial Management: A Case Study of a Local Government in Indonesia - Cahyono, Budi (Curtin University, 2017)
Utilising content analysis of external audit reports published between 2009 and 2014, this study identified systemic problems resulting from non-compliance in public financial management (PFM) operations of local governments in Indonesia. Further, a single case study was conducted to investigate factors for non-compliance and how they influence the PFM actors to be involved in non-compliance practices. Findings of this study suggested that employees’ motives and dysfunctional bureaucratic structures have contributed to the emergence of non-compliance.